What EFL Students Think about Methods Used to Instruct Their Language - Andi Asrifan; Heriyanti (UNIB Press, 2023)
EFL classes are offered at the secondary school level in Indonesia. To ensure the success of the English as a Foreign Language (EFL) classroom, educators in the field must use effective pedagogical practices. Assessing teachers' performance in the classroom can have far-reaching implications on the quality of education in the classroom. A useful strategy is to analyze the pupils' perspectives. Research was therefore done to detail which techniques students found useful and which they found less, as well as the reasons behind these judgments. Twenty-nine college students participated in this study via a systematic random sampling strategy. Focus group discussion (FGD) was used to collect data, which was then analyzed descriptively using a qualitative methodology. First, the analysis revealed that (1) students viewed the Communicative Method, Cooperative Learning, the Competency-Based approach, and Community Language Learning as effective strategies for teaching and learning languages. While the Lecturing Method, the Grammar-Translation Method, the Direct Method, and the Task-Based Method are all considered inefficient. (2) The strategies that students found useful and those that they found ineffective. (3) Three distinct senses will recognize an efficient strategy. These include studying outside the class, reviewing material from the previous session, and repeating it before moving on to the new one.